Under five, under-educated? - David, Tricia (Milton Keynes [England]: Open University Press, 1990)
An examination of the historical and social factors which have delayed the development of comprehensive and co-ordinated pre-school provision. The book explores the importance of continuity, the formation of attachments and the roles of parents and pre-school workers.
Keywords: Education